Study on the Effects of Main Error Factor on the Transmission Characteristic of RV Reducer - Zhao Daxing; Yuan Kang; Wu Zhenyu; Chen Shaonan (Jixie chuandong)
The three-dimensional parametric models of RV reducer are constructed by using SolidWorks software,and then the model is imported into ADAMS software,a batch of dynamic models are established and simulated by macro program,and the exporting data of rotation speed and rotation angle is imported into Matlab.After data processing,the transmission error and the fluctuation of rotation speed that is the variance of the rotation speed are calculated. The simulation result shows that under the condition of the variation of error value is the same,decreasing the radius of gear pin and increasing the value of modification of positive equidistance,the value of fluctuation of rotation speed will increase greatly,increasing the value of the modification of negative moved distance and modification of negative equidistance, it will decrease less. For transmission error,decreasing the radius of gear pin and increasing the value of the value of modification of positive equidistance,it will increase greatly,increasing the value of the eccentricity of pin wheel has tiny influence on it.